Cultivation and flocculation efficiency for biomass harvesting of freshwater microalga, Scenedesmus dimorphus utex 1237 - Saiful Shafrie Shamsul Azhar. (2015)
Freshwater microalga, Scenedesmus dimorphus UTEX 1237 strain is usually involved in the production of biofuel due to its high lipid content. The productivity and lipid content are depending on the culture conditions and growth medium. The selection of suitable growth medium that can produce high cell concentration of Scenedesmus dimorphus in short time period is necessary. Besides that, an economical and efficient harvesting technique of microalgae is essential to effectively recover the microalgae cells. Thus, this study was performed to select the suitable of microalgae growth media to produce high cell concentration of microalga, Scenedesmus dimorphus UTEX 1237 in short time period, and to evaluate the flocculation efficiency of different types of flocculants towards microalgae harvesting. Scenedesmus dimorphus was cultivated in the shake flasks employing three types of fresh water algae media, i.e., TAP, Modified BG-11 with urea, and Modified CHU-13 for 14 days. The environmental conditions including light, temperature and agitation speed was standardized for all culture. The growth rate was measured using optical density and cell counting using haemocytometer. The best medium for growth was then used in the scaled up production of microalga in 1L and 2L custom photobioreactors. Subsequently, the flocculation efficiency experiments were conducted by adjusting the pH of the culture medium using either 2M NaOH or 2M HCl, and by applying different dosages of IV biopolymer chitosan and ferric chloride. The result shows that Scenedesmus dimorphus UTEX 1237 cultivated in TAP media had shown the highest optical density and cell number, with 2.87±0.02 at 680nm and 3.32x107 cell/mL, respectively. The flocculation efficiency of S. dimorphus reached up to 67.6% when culture pH was adjusted to 12.5. Flocculation efficiency of S. dimorphus increased to 98.6% when adding 0.02 g/L FeCl3 as flocculants at pH 8.12, whereas the flocculation experiment on of S. dimorphus with biopolymer chitosan at pH 7.4 produced about 98% of flocculation efficiency. From these findings, it can be concluded that different types of growth media affects the growth rate of microalgae species differently, and different types of flocculants gives different flocculation efficiencies.